Spironolactone effect on the blood pressure of patients at risk of developing heart failure: an analysis from the HOMAGE trial - Ferreira, João Pedro; Collier, Timothy; Clark, Andrew L; Mamas, Mamas A; Rocca, Hans-Peter Brunner-La; Heymans, Stephane; González, Arantxa; Ahmed, Fozia Z; Petutschnigg, Johannes; Mujaj, Blerim; Cuthbert, Joe; Rouet, Philippe; et al. (European heart journal. Cardiovascular pharmacotherapy, 2022)
Abstract Aims Uncontrolled blood pressure (BP) increases the risk of developing heart failure (HF). The effect of spironolactone on BP of patients at risk of developing HF is yet to be determined. To evaluate the effect of spironolactone on the BP of patients at risk for HF and whether renin can predict spironolactone’s effect. Methods and results HOMAGE (Heart OMics in Aging) was a prospective multicentre randomized open-label blinded endpoint (PROBE) trial including 527 patients at risk for developing HF randomly assigned to either spironolactone (25–50 mg/day) or usual care alone for a maximum of 9 months. Sitting BP was assessed at baseline, Months 1 and 9 (or last visit). Analysis of covariance (ANCOVA), mixed effects models, and structural modelling equations was used. The median (percentile25–75) age was 73 (69–79) years, 26% were female, and >75% had history of hypertension. Overall, the baseline BP was 142/78 mmHg. Patients with higher BP were older, more likely to have diabetes and less likely to have coronary artery disease, had greater left ventricular mass (LVM), and left atrial volume (LAV). Compared with usual care, by last visit, spironolactone changed SBP by −10.3 (−13.0 to −7.5) mmHg and DBP by −3.2 (−4.8 to −1.7) mmHg (P < 0.001 for both). A higher proportion of patients on spironolactone had controlled BP <130/80 mmHg (36 vs. 26%; P = 0.014). Lower baseline renin levels predicted a greater response to spironolactone (interactionP = 0.041). Conclusion Spironolactone had a clinically important BP-lowering effect. Spironolactone should be considered for lowering blood pressure in patients who are at risk of developing HF.